Shipping Container Logistics and Allocation - Lai, K. K.; Lam, Kokin; Chan, W. K. (The Journal of the Operational Research Society, 1995)
A major shipping company in Hong Kong is faced with several logistical and allocation problems. It needs to find a better way to allocate empty containers that are transported from the Middle East to ports in the Far East, subject to vessel schedules and capacities. It needs to know what to do when the supply of empty containers is less than the demand, and it needs to determine the mix of container types that the company should maintain in the long run. To deal with these challenges, a simulation model of the shipping company's operational activities was developed. Heuristic search was employed to identify the policies that yield the lowest operating cost in terms of leasing, storage, pick-up, drop-off and other charges. What makes the problem difficult is that the forecasts of future export movement as well as the demand for empty containers change continually and the company is faced with the possibility of lost sales if containers are not available when requested by customers. This study provided insights that resulted in substantial savings to the shipping company while increasing customers' satisfaction.